2005
DOI: 10.1016/j.jacc.2005.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Atrial Fibrillation on the Diagnostic Performance of B-Type Natriuretic Peptide Concentration in Dyspneic Patients

Abstract: In patients without, but not in those with HF, the presence of AF is associated with higher circulating BNP levels, suggesting that a higher diagnostic threshold should be used in patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 37 publications
10
104
1
1
Order By: Relevance
“…All known factors that influence natriuretic peptide concentrations in the absence of HF (15)(16)(17). Furthermore, the 1-year mortality in our cohort of 28.0% was substantially higher than the 15.1% mortality reported from the Pro-BNP Investigation of Dyspnea in the Emergency Department (PRIDE) study, again suggesting that the population reported in this study was overall more "ill" than those of previously published studies (18 ).…”
Section: Discussioncontrasting
confidence: 43%
“…All known factors that influence natriuretic peptide concentrations in the absence of HF (15)(16)(17). Furthermore, the 1-year mortality in our cohort of 28.0% was substantially higher than the 15.1% mortality reported from the Pro-BNP Investigation of Dyspnea in the Emergency Department (PRIDE) study, again suggesting that the population reported in this study was overall more "ill" than those of previously published studies (18 ).…”
Section: Discussioncontrasting
confidence: 43%
“…Some studies have demonstrated that atrial fibrillation can cause elevated BNP levels (36), whereas others have demonstrated that atrial fibrillation in isolation does not cause BNP elevation (37). Another potential limitation to the use of BNP is in patients who are obese (body mass index of 30 kg/m 2 or greater).…”
Section: Bnp Versus Nt-probnpmentioning
confidence: 99%
“…Because the distribution pattern of plasma BNP values did not appear to be normal, and the values were considerably shifted to one side, the values were transformed into a common logarithm (LogBNP) [30]. Data are expressed as mean±SD range.…”
Section: Statisticsmentioning
confidence: 99%